2013
DOI: 10.1038/jcbfm.2013.145
|View full text |Cite
|
Sign up to set email alerts
|

Functional Hyperemia and Mechanisms of Neurovascular Coupling in the Retinal Vasculature

Abstract: The retinal vasculature supplies cells of the inner and middle layers of the retina with oxygen and nutrients. Photic stimulation dilates retinal arterioles producing blood flow increases, a response termed functional hyperemia. Despite recent advances, the neurovascular coupling mechanisms mediating the functional hyperemia response in the retina remain unclear. In this review, the retinal functional hyperemia response is described, and the cellular mechanisms that may mediate the response are assessed. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
168
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(177 citation statements)
references
References 112 publications
(165 reference statements)
4
168
1
4
Order By: Relevance
“…The exact pathways involved in neuro-glia-vascular coupling are not fully understood. Likely, oxygen demand in response to flicker light increases [62] and stimulated neurons signal a calcium concentration surge in Müller glia that release vasodilatory prostaglandin E2, NO, and epoxyeicosatrienoic acids [63,64]. The gliovascular unit, thus, relaxes the smallest arteriolar walls.…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…The exact pathways involved in neuro-glia-vascular coupling are not fully understood. Likely, oxygen demand in response to flicker light increases [62] and stimulated neurons signal a calcium concentration surge in Müller glia that release vasodilatory prostaglandin E2, NO, and epoxyeicosatrienoic acids [63,64]. The gliovascular unit, thus, relaxes the smallest arteriolar walls.…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…Suramin, a non-selective purinergic antagonist completely blocks , which converts membrane phospholipids (MPL) to arachidonic acid (AA) which is subsequently metabolized to the vasodilators prostaglandin E 2 (PGE 2 ) and epoxyeicosatrienoic acids (EETs), and to the vasoconstrictor 20-hydroxy-eicosatetraenoic acid (20-HETE). (a -f ) From Metea & Newman [18] and (g) adapted from Newman [20]. (Online version in colour.…”
Section: Glial Release Of Arachidonic Acid Metabolites Mediates Neuromentioning
confidence: 99%
“…One question is whether the visible laser beam will affect retinal physiology, particularly when using vis-OCT to perform quantitative measurements such as blood flow and sO 2 . It has been found that both flow and retinal metabolism change when the retina transitions from dark adaptation to light or under flicker stimulation [31][32][33]; however, we do not expect such changes to occur when the retina has already been light-adapted [34,35]. The additional exposure from vis-OCT is unlikely to change the physiological condition of the eye, thereby underscoring the importance of ensuring the patient's eye is light-adapted before vis-OCT imaging.…”
Section: Discussionmentioning
confidence: 99%